Feasibility Analysis of The First Grade High School Biological Textbook: Evaluating Environmental Literacy Aspect in High School Students Around of Bahorok District - Rika Armiati; Syarifah Widya Ulfa (Universitas Labuhanbatu, 2025)
The activity to determine the completeness and suitability of the content of the book material being analyzed, even though the books published and used by the school have passed validation tests both in terms of material content, completeness of material and images, as well as supporting learning. Evaluating the feasibility of biology textbook content in terms of environmental literacy is crucial to ensure that the presented materials go beyond fundamental biological concepts and effectively foster students’ awareness and competencies in responding to environmental challenges. This research aims to evaluate the feasibility of biology textbook content from the perspective of environmental literacy, specifically examining 2 biology textbooks of first Grade high school which published by Grafindo Media Pratama and Erlangga, which are utilized in the teaching and learning process. This research uses quantitative methods with data analysis in this research using descriptive statistics. Assessment of Environmental Aspects in Textbook I and Textbook II for High School Biology has a score of 35.55 with fairly good criteria according to the assessment criteria. Environmental literacy that appears frequently in the analyzed biology textbooks is knowledge of ecology and natural history as well as knowledge of environmental problems and issues. This study reveals that while biology textbooks emphasize cognitive aspects of environmental literacy, they lack affective and contextual content essential for fostering responsible environmental behavior. Its novelty lies in the localized analysis of textbook content, highlighting gaps rarely addressed in existing research